1995
DOI: 10.1016/0005-2728(94)00188-b
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Ca2+ of the hydrolysis and the synthesis of ATP in Ehrlich ascites tumour mitochondria: relation to the Crabtree effect

Abstract: Phosphorylation of ADP and hydrolysis of ATP by isolated mitochondria from Ehrlich ascites tumour cells is greatly reduced when the mitochondria have been preloaded with Ca2+ (50 nmol/mg protein or more). Translocation of ADP is diminished in Ca(2+)-loaded mitochondria. However, ATPase in toluene-permeabilized mitochondria and in inside-out submitochondrial particles is also strongly inhibited by micromolar concentrations of Ca2+, indicating that, independently of adenine nucleotide transport, F1Fo-ATPase is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…Hormone-evoked increases in ΔΨ m and ΔpH m occurred even in the presence of oligomycin to block proton flux through the F1-Fo ATP synthetase. These results indicate that the prolonged increase in mitochondrial PMF could not be explained by Ca 2+ -dependent inhibition of proton flux through the Fo subunit, as observed in some tumor cells [44]. …”
Section: Stimulus-evoked Increases In Mitochondrial Proton Motive Forcementioning
confidence: 77%
“…Hormone-evoked increases in ΔΨ m and ΔpH m occurred even in the presence of oligomycin to block proton flux through the F1-Fo ATP synthetase. These results indicate that the prolonged increase in mitochondrial PMF could not be explained by Ca 2+ -dependent inhibition of proton flux through the Fo subunit, as observed in some tumor cells [44]. …”
Section: Stimulus-evoked Increases In Mitochondrial Proton Motive Forcementioning
confidence: 77%
“…Alternatively, elevation in PMF could result from the inhibition of pathways that dissipate H + gradient. It has been reported that mitochondrial Ca 2+ uptake may inhibit ATP synthase [50] consequently increasing PMF and reducing ATP level. However, our observations with FCCP and oligomycin as well higher ATP content detected in _2 line (yet unpublished) rather exclude ATP synthase inhibition as a mechanism of PMF increase.…”
Section: Discussionmentioning
confidence: 99%
“…This ‘after-hyperpolarization’ parallels a significant increase in the ROS release from mitochondria [143]. The mechanism of the relative hyperpolarization following depolarization by moderate Ca 2+ load is yet to be clarified but could be related to inhibition of the adenylate translocase [148] or F 0 F 1 -ATPase by Ca 2+ [149,150]. Nonetheless, the stimulated ROS generation under this condition is most likely due to a shift of ΔΨ towards higher values, into the range where ROS generation is sensitive to changes in ΔΨ.…”
Section: Dependence On δψ Of the Effect Of Ca2+ On Ros Generationmentioning
confidence: 99%